2007
DOI: 10.1007/s10856-006-0681-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of porosity and fibre diameter on the degradation of chitosan fibre-mesh scaffolds and cell adhesion

Abstract: The state of the art approaches for tailoring the degradation of chitosan scaffolds are based on altering the chemical structure of the polymer. Nevertheless, such alterations may lead to changes in other properties of scaffolds, such as the ability to promote cell adhesion. The aim of this study was to investigate the influence of physical parameters such as porosity and fibre diameter on the degradation of chitosan fibre-mesh scaffolds, as a possible way of tailoring the degradation of such scaffolds. Four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 23 publications
5
25
0
Order By: Relevance
“…21 Cunha-Reis et al showed cell adhesion consistent with the nature of the HDD material used in this study. 22 In our study, sites receiving the HDD had improved postoperative healing with minimal complications when compared to the control site. This may be attributed to the antibacterial properties of chitosan, which have been investigated in vitro studies.…”
Section: Discussionsupporting
confidence: 49%
“…21 Cunha-Reis et al showed cell adhesion consistent with the nature of the HDD material used in this study. 22 In our study, sites receiving the HDD had improved postoperative healing with minimal complications when compared to the control site. This may be attributed to the antibacterial properties of chitosan, which have been investigated in vitro studies.…”
Section: Discussionsupporting
confidence: 49%
“…The platform used in this work was Ch, because it has been extensively studied by us and others, both in terms of processing techniques as well as cellular response [31,32,39,40], including osteoblastic [32] and immune cell behavior in vitro [26], and local inflammatory reaction in vivo [38]. Ch has also been investigated in the context of bone regeneration, both in vitro and in vivo [32,41].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, both a high surface area and an interconnected three‐dimensional (3D) porous structure are essential (Antunes et al, ; Gomes et al ., ). Proper geometry and pore dimensions are also factors that can significantly affect cellular behaviour (Cunha‐Reis et al, ; Gomes et al, ). Additionally, scaffold architecture is very important and affects cell attachment, proliferation and differentiation (Guo et al, ; Barnes et al, ; Agarwal et al, , ).…”
Section: Introductionmentioning
confidence: 99%